LiSEQ – whole-genome sequencing of a cross-sectional survey of Listeria monocytogenes in ready-to-eat foods and human clinical cases in Europe. Issue 2 (18th February 2019) - Painset, Anaïs; Björkman, Jonas T.; Kiil, Kristoffer; Guillier, Laurent; Mariet, Jean-François; Félix, Benjamin; Amar, Corinne; Rotariu, Ovidiu; Roussel, Sophie; Perez-Reche, Francisco; Brisse, Sylvain; Moura, Alexandra; et al.
Abstract : We present the LiSEQ (Listeria SEQuencing) project, funded by the European Food Safety Agency (EFSA) to compare Listeria monocytogenes isolates collected in the European Union from ready-to-eat foods, compartments along the food chain (e.g. food-producing animals, food-processing environments) and humans. In this article, we report the molecular characterization of a selection of this data set employing whole-genome sequencing analysis. We present an overview of the strain diversity observed in different sampled sources, and characterize the isolates based on their virulence and resistance profile. We integrate into our analysis the global L. monocytogenes genome collection described by Moura and colleagues in 2016 to assess the representativeness of the LiSEQ collection in the context of known L. monocytogenes strain diversity.